IDO1 Inhibitor RY103 Suppresses Trp-GCN2-Mediated Angiogenesis and Counters Immunosuppression in Glioblastoma - Zikang Xing; Xuewen Li; Zhen Ning Tony He; Xin Fang; Heng Liang; Chunxiang Kuang; Aiying Li; Qing Yang (Pharmaceutics, 2024)
Glioma is characterized by strong immunosuppression and excessive angiogenesis. Based on existing reports, it can be speculated that the resistance to anti-angiogenic drug vascular endothelial growth factor A (VEGFA) antibody correlates to the induction of novel immune checkpoint indoleamine 2,3-dioxygenase 1 (IDO1), while IDO1 has also been suggested to be related to tumor angiogenesis. Herein, we aim to clarify the potential role of IDO1 in glioma angiogenesis and the mechanism behind it. Bioinformatic analyses showed that the expressions of IDO1 and angiogenesis markers VEGFA and CD34 were positively correlated and increased with pathological grade in glioma. IDO1-overexpression-derived-tryptophan depletion activated the general control nonderepressible 2 (GCN2) pathway and upregulated VEGFA in glioma cells. The tube formation ability of angiogenesis model cells could be inhibited by IDO1 inhibitors and influenced by the activity and expression of IDO1 in condition medium. A significant increase in serum VEGFA concentration and tumor CD34 expression was observed in IDO1-overexpressing GL261 subcutaneous glioma-bearing mice. IDO1 inhibitor RY103 showed positive anti-tumor efficacy, including the anti-angiogenesis effect and upregulation of natural killer cells in GL261 glioma-bearing mice. As expected, the combination of RY103 and anti-angiogenesis agent sunitinib was proved to be a better therapeutic strategy than either monotherapy.